Of Young People and Internet Cafés - Xiao, ZhiMin; Higgins, Steve (Frontiers in Psychology, 2021)
This study examines how adolescent experience in Internet cafés (known as wangba in Chinese) relates to academic attainment in urban, rural, and Tibetan schools of China. By documenting the frustrations teenagers express in their negotiations with adults surrounding access to and use of wangba and, by comparing self-reported academic standing of students from similar backgrounds with how they differ in their experience in wangba, the study finds that visiting wangba is not strongly correlated with the probability of students reporting either high- or under-achievement. While students without any experience in wangba are substantially less likely to report academic underperformance, the association disappears after matching when the logit regression model is less model-dependent and vulnerable to the problems associated with missing data. The paper concludes that visiting wangba alone is not systematically correlated with academic attainment, and that much adult anxiety concerning adolescent visit to wangba represents moral-technological panic and, offers a simplified explanation for educational problems that have deep macrosocial roots.